2017
DOI: 10.3389/fneur.2017.00607
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Motor Symptoms across Different Motor Tasks, Quantified via Random Forest Feature Classification in Parkinson’s Disease

Abstract: BackgroundObjective assessments of Parkinson’s disease (PD) patients’ motor state using motion capture techniques are still rarely used in clinical practice, even though they may improve clinical management. One major obstacle relates to the large dimensionality of motor abnormalities in PD. We aimed to extract global motor performance measures covering different everyday motor tasks, as a function of a clinical intervention, i.e., deep brain stimulation (DBS) of the subthalamic nucleus.MethodsWe followed a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
11
0
3
Order By: Relevance
“…In a previous study, we showed that machine-learning approaches significantly correlate with known clinical measures such as the UPDRS (Kuhner et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, we showed that machine-learning approaches significantly correlate with known clinical measures such as the UPDRS (Kuhner et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…There is already evidence that jerk is abnormal in PD (Teulings et al, 1997;Hogan and Sternad, 2009). Other methods of data reduction by feature extraction involve signal processing methods, e.g., wavelet analysis (Joshi et al, 2017), stochastic models, like the Hidden Markov Model (Joshi et al, 2017), or machine-learning algorithms (Wouda et al, 2016), i.e., using Random Forests (Wahid et al, 2015;Kuhner et al, 2016Kuhner et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, these models have been used to predict the optimal stimulation frequency after the DBS implantation surgery based on the Unified Parkinson's disease Rating Scale (UPDRS III) scores collected at or before surgery (Khojandi et al, 2017 ) These models have also shown promise when used on the data collected from wearable sensors. Kuhner et al ( 2017 ) captured 3D inertial measurements from a motion capture suit consisting of magnetometers, accelerometers, and gyroscopes in PD patients with DBS switched-off or -on, as well as healthy controls. Utilizing an RF model with probability distribution on data derived from various clinical tasks, they demonstrated the ability to detect PD patients off DBS from healthy subjects with high sensitivity and specificity.…”
Section: Decision Trees and Random Forest Algorithmsmentioning
confidence: 99%
“…DBS technique has been known for 30 years, and over the past few years a number of interdisciplinary works concerning the use of machine learning methods have appeared, extending its functionality. Kuhner et al (2017) used Random Forests with probability distributions to detect abnormal motor behaviour of PD patients performing several different motor tasks in two clinical conditions (DBS switch: off, on). Trevathan et al (2017) Shamir et al (2015) proposed a clinical support decision system to provide effective stimulation and adequate drug dosages, based on three machine learning methods, which included Support Vector Machines, Naïve Bayes, and Random Forest.…”
Section: Machine Learning Approach Used In Dbsmentioning
confidence: 99%